HIV/AIDS in Pakistan: the context and magnitude of an emerging threat. Issue 9 (September 1998) - Hyder, A A; Khan, O A
Abstract : STUDY OBJECTIVE: The objectives of this review were to: (1) assess the nature and comprehensiveness of information regarding HIV/AIDS in Pakistan; (2) to evaluate the extent of HIV/AIDS in Pakistan by epidemiological estimates; (3) to indicate the implications of the results for health policy in Pakistan and other regions at a similar stage in the epidemic. DESIGN: A structured review of published, unpublished, and government literature was undertaken to collate all available information and present a descriptive epidemiological profile of HIV/AIDS in the country. SETTING: Pakistan, a developing country in the South Asian region. National and regional information and analysis are presented in so far as the data allowed. Sample sizes varied from 1.35 million people screened at the national level to smaller studies of fewer than 100 screened. RESULTS: Data pertaining to HIV/AIDS in Pakistan showed the best national estimates of HIV prevalence as 64 per 100, 000 (0.064%). Within patients with sexually transmitted diseases the seroprevalence was as high as 6100 per 100, 000 (6.1%); in men with extramarital contacts, 5400 per 100, 000 (5.4%) and was as low as zero in some studied populations as well. The average age of onset was reported as 30 years. It is estimated that if all incident cases of AIDS were to die, there would be at least 5000 deaths annually attributable to HIV/AIDS. CONCLUSION: Coupled with the extremely low awareness of HIV/AIDS in Pakistan, as well as growing number of cases, the AIDS epidemic is poised to take a hold in Pakistan. The presence of additional risk factors such as unscreened blood, and low condom use rates make the situation fertile for AIDS to become a major public health issue. Pakistan's health policy must be proactive in tackling this emerging health threat.